"Research into Improving the Business Processes of the Maintenance and Inventory Control Unit." (Case Study, Golden Tulip Hotel, Kumasi City.) - Asense, Phanuel Seli Kwadzo (2011)
A Dissertation presented to the Institute in partial fulfilment of the requirement for the award of the Degree of Master of Science in Advanced ICT Studies (Management Option)